Perbandingan Hygiene Menstruasi Pada Wanita Usia Reproduksi Antara yang menggunakan Pembalut Dengan Menstrual Cup - Mira Rusdiana; Achmad Fauzi (Risenologi, 2022)
Hygiene is a component of hygiene that has a significant influence in defining a person's health state, particularly in preventing infection of the reproductive organs. During menstruation, women utilize menstrual products to absorb the blood that is expelled. The most prevalent period products include disposable pads, tampons, cloth pads, and menstrual cups. Inadequate personal cleanliness and infrequent changes of sanitary napkins result in prolonged blood contact with the vagina, making it susceptible to bacterial infection. The alternative to the menstrual cup is regarded as the most effective method for collecting menstrual blood due to its ability to reduce fishy odors and the occurrence of infection, irritation, and rashes. Determine whether or not there is comparison hygiene between those who use sanitary napkins and menstrual cups. This research is included in the type of non-experimental research and comparative research design which aims to compare one group with another group. Based on the results of the study the average value of hygiene in sanitary napkin users was 38.80, and the average value of hygiene using menstrual cups was 41.00, statistical test results p-value 0.021<0.05. The conclusion show there are differences in results hygiene on the use of sanitary pad with menstrual cups, where the average results obtained hygiene menstrual menstrual cups are better than hygiene on those using sanitary pad.